Pengaruh Pelatihan Kerja Terhadap Kinerja Karyawan Pada Akademi Pariwista Medan Hotel School Medan - Susi Marta Tambunan (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2021)
Facing change and competition both at the national and international levels, then employees must adapt to changes in technology, such as the emergence of new technology or new work methods in the company. Medan Hotel School Tourism Academy, which is a private tertiary institution where employees in carrying out their duties and responsibilities still require training from the university as well as from the Higher Education Service Institution (LLDIKTI). But the problem in this study is training has an effect on improving employee performance at the Medan Hotel School of Tourism Academy, Medan? This type of research is a qualitative descriptive study. Methods of data collection are done through interviews, documentation and questionnaires. The number of samples in this study were 16 people with the determination technique is total sampling. The hypothesis in this study is to estimate the effect of job training on employee performance at the Medan Hotel School of Tourism, Medan. 1. Job training has an effect on employee performance at the Medan Hotel School Tourism Academy, Medan. 2. The most dominant indicator of job training in influencing the performance of employees at the Medan Hotel School Tourism Academy, Medan is that after participating in training, employees are able to complete work more easily and quickly, 3. The employee performance indicator that has the most dominant impact is the job training conducted by Medan Tourism Academy Hotel School, Medan are employees in carrying out and completing their work on time.